IMPACT OF ONSITE HEALTH CARE CENTERS ON JOB SATISFACTION IN ARMED CONFLICT SOCIETIES: THE ZIMBABWEAN WAR OF LIBERATION PERSPECTIVE - Takupiwa NYANGA; Rosemary SIBANDA (Business Excellence and Management, 2019)
Employee wellness is one of the key and most essential antecedents to employee and organizational performance. Organisational performance heavily depends on the health and wellness of employees and their attitude towards their work. The study explored the relationship between wellness programs and job satisfaction for workers in armed conflict societies. The study focused on one wellness program; that is the establishment of organizational onsite health centers. A quantitative research methodology was employed to carry out the study. A questionnaire was used to solicit data from 50 people who witnessed or directly or indirectly participated in the war of liberation in Zimbabwe and the civil war in Mozambique. Descriptive statistics was used to analyze the collected data. The study established that there is a strong relationship between the establishment of onsite health centers and job satisfaction. All the major services of health clinics such as provision of health services to the injured during the war, provision of counseling services, provision of physical fitness programs and provision of ill-health prevention services showed a strong relationship with job satisfaction. It was recommended that all organizations operating in armed conflict societies should establish health centers within their premises to provide health services to the physically and emotionally injured employees.